1993
DOI: 10.1021/bi00210a042
|View full text |Cite
|
Sign up to set email alerts
|

Electron self-exchange in high-potential iron-sulfur proteins. Characterization of protein I from Ectothiorhodospira vacuolata

Abstract: During previous research on oxidized and reduced high-potential iron-sulfur proteins (HiPIP hereafter), qualitative different electron self-exchange rates were noticed. We have now investigated this phenomenon in detail for HiPIP I and II from Ectothiorhodospira vacuolata, which differ significantly in total charge and in which the sequence homology is the largest among all known HiPIPs. We have also characterized the electronic structure of HiPIP I through 1H NMR and EPR spectroscopies to parallel the existin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 53 publications
1
31
0
Order By: Relevance
“…6 we show the experimental points obtained using the T,' values for oxidized RJ ferrnentuns and E. halophila iso-11 HiPIPs measured in this work, and previously reported values for C. vinosum [63], R. gelutinosus 1661, R. globiformis [28], and E. vucuolatu iso-I [67] and iso-I1 [29] HiPIPs. We have assumed for E. halophila iso-I1 HiPIP the same geometry as found for E. halophila iso-I HiPIP [41], for R. gelutinosus and for RJ: ferrnentans HiPIPs the geometry of C. vinosum HiPIP [65], and for E. vucuoluta iso-I HiPIP the geometry of E. vucuolatu iso-I1 HiPIP 1431.…”
Section: Analysis Of T;' Values For Cysteine Protons Of Oxidizedsupporting
confidence: 64%
“…6 we show the experimental points obtained using the T,' values for oxidized RJ ferrnentuns and E. halophila iso-11 HiPIPs measured in this work, and previously reported values for C. vinosum [63], R. gelutinosus 1661, R. globiformis [28], and E. vucuolatu iso-I [67] and iso-I1 [29] HiPIPs. We have assumed for E. halophila iso-I1 HiPIP the same geometry as found for E. halophila iso-I HiPIP [41], for R. gelutinosus and for RJ: ferrnentans HiPIPs the geometry of C. vinosum HiPIP [65], and for E. vucuoluta iso-I HiPIP the geometry of E. vucuolatu iso-I1 HiPIP 1431.…”
Section: Analysis Of T;' Values For Cysteine Protons Of Oxidizedsupporting
confidence: 64%
“…This hydrophobic patch is conserved among the three-dimensional structures of HiPIPs of other species. Spectroscopic study has shown that HiPIPs are capable of forming temporary dimers in solution by using the hydrophobic surface and that the electron transfer can occur between the two monomers in the dimeric structure (53,54), suggesting that the HiPIP monomer in solution interacts temporally with the other protein via its hydrophobic patch to transfer electrons.…”
Section: Resultsmentioning
confidence: 99%
“…Ferricyanide oxidation of a number of [4Fe-4S] proteins leads to EPR signals with either an average gЈ value (g av ) of ϳ2.01 and narrow ⌬g range, as exemplified by A. vinlandii FdI (26), endonuclease III (27), and aconitase (13), or to a broader signal covering the gЈ value range from ϳ2.12 to 2.02, found for HiPiPs (24,42). The EPR spectra of oxidized RumA (Fig.…”
Section: Discussionmentioning
confidence: 99%